Ankle arthrodesis via a transfibular approach and circular external fixation - Pereira, Vinícius Felipe; Masuda, Vitor Yoshiura; Boatto, Hilário; Pereira Junior, Hélio da Cunha; Fernandes Junior, José Carlos Figueiredo; Mansur, Nacime Salomão Barbachan (Scientific Journal of the Foot & Ankle, 2019)
Objective: To present the radiographic and functional outcomes of a series of 11 cases of ankle arthrodesis performed with a circular external fixator using the Ilizarov method and a transfusion approach, conducted between January 2017 and June 2018. Methods: The patients were evaluated according to American Orthopedic Foot and Ankle Society (AOFAS) and visual analogue scale (VAS) scores. Ankle radiographs were evaluated on anteroposterior and profile views. All patients underwent a similar procedure regarding the surgical approach and assembly of the Ilizarov apparatus. Results: Eleven patients, with a mean age of 44.81 years (28-70 years), underwent surgery. The average follow-up time was 50.81 weeks (13-90 weeks). The main indication for surgery was post-traumatic secondary arthritis. The mean functional AOFAS score was 55.72 (45-64) points. An evaluation of the soft tissues revealed surgical wound healing of the transfibular approach in 9 patients (81%). All cases showed signs of superficial pin- or wire-tract infection. Union was reported in 10 patients (90.9%), and the radiographic varus deformities found in 2 patients did not exceed 7º. No additional surgical procedure was required during follow-up. Conclusion: Ankle arthrodesis performed by a transfibular approach and fixation performed by the Ilizarov method were efficient, promoted the functional restoration of the patient, considering the complexity of the cases, and resulted in a high union rate. Level of Evidence IV; Therapeutic Studies; Case Series.